Polyphenol Extraction from Musa corniculata Peel Using Microwave Assisted Extraction (MAE) Method with Ethanol Solvent - Rahmawati, Istiqomah; Sa’roni, Achmad; Wardhani, Maharani Tri; Fachri, Boy Arief; Palupi, Bekti; Rizkiana, Meta Fitri; Amini, Helda Wika; Reza, Muhammad (Universitas Jember, 2024)
Banana peel (Musa corniculata) is one of the superior plants in Indonesia which is rich in polyphenolic compounds as a source of antioxidants. The potential of polyphenolic compounds as antioxidants can be used as an alternative to reduce banana peel waste. This study aims to determine the total content of polyphenols and antioxidant activity of horn banana peel extract. Extraction used the Microwave Assisted Extraction (MAE) method with ethanol solvent and the variables were extraction time (4, 7, and 10 minutes), solvent concentration (50, 73 and 96 %), ratio of simplicia mass to solvent volume (1:12, 1 :8, 1:6 g/mL) with a microwave power of 150 Watt. Determination of polyphenol content using the Folin-Ciocalteau method and the ability of polyphenols as antioxidants were analyzed by DPPH test. This study used the Design Expert 13 Response Surface Methodology software, the Box Behnken type, to determine the extraction parameters for the total polyphenol content. The highest total polyphenol content was obtained at 354.02 mg GAE/g from the combination of parameters 50% solvent concentration, 10 minutes extraction time, and the ratio of horn banana peel powder to 1:8 g/mL solvent.